Meta-analysis: Effectiveness of long- and short-term albendazole therapy for intraparenchymal neurocysticercosis - Jerves Serrano, Teodoro Edmundo (2018)
Objective: To determine the effectiveness of long- and short-term albendazole therapy in adults and children with cystic and transitional parenchymal neurocysticercosis confirmed by neuroimaging. Materials and methods: A meta-analysis was performed using clinical trials from MEDLINE and LILACS with a Jadad score > 2. Additional studies were not found on ClinicalTrials.gov and ResearchGate. The main endpoint was the persistence of radiological lesions and the secondary endpoint was the presence of adverse effects. Pooled relative risks (RR) and 95 % confidence intervals were calculated for both endpoints using the Mantel-Haenszel fixed-effects model. The analysis was conducted using software Stata 11. Heterogeneity was assessed by chi-square test and a value of p < 0.10 was considered statistically significant. Publication bias was estimated by sensitivity analysis and Egger’s test. Results: Four studies were included. There was no difference between long- and short-term albendazole therapies for neurocysticercosis. Pooled RR of the persistence of radiological lesions after short-term vs. long-term therapy was 1.05 (95 % CI 0.72-1.54). Mantel-Haenszel test showed a p-value of 0.789. Moreover, both the sensitivity analysis and Egger’s test supported the absence of publication bias. No significant difference was noticed regarding the adverse effects. Conclusions: Evidence suggests that there is no difference between short- and long-term therapies for single transitional parenchymal lesions; therefore short-term therapy may be used effectively.